Reducing Quorum Sensing-Mediated Virulence Factor Expression and Biofilm Formation in Hafnia alvei by Using the Potential Quorum Sensing Inhibitor L-Carvone - Li, Tingting; Mei, Yongchao; He, Binbin; Sun, Xiaojia; Li, Jianrong (Frontiers in Microbiology, 2019)
Quorum sensing (QS), one of the most remarkable microbiological discoveries, is considered a global gene regulatory mechanism for various traits in bacteria, including virulence and spoilage. Hafnia alvei, an opportunistic pathogen and a dominant psychrophile, uses the lux-type QS system to regulate the production of virulence factors and biofilms, which are harmful to the food industry. Based on the QS interference approach, this study aimed to reveal the efficacy of L-carvone at sublethal concentrations on QS-regulated virulence factors and biofilm formation in H. alvei. QS inhibitory activity was demonstrated by the reduction in swinging motility (61.49%), swarming motility (74.94%), biofilm formation (52.41%) and acyl-homoserine lactone (AHL) production (0.5 μL/mL). Additionally, molecular docking and RT-qPCR studies for AHL synthase HalI and QS transcriptional regulator HalR revealed a plausible molecular mechanism for QS inhibition by L-carvone. These findings suggest that L-carvone (a main component of spearmint essential oils) could be used as a novel quorum sensing inhibitor to control H. alvei in the food industry.